2009
DOI: 10.1016/j.eurpsy.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy for personality disorders: Short-term day hospital psychotherapy versus outpatient individual therapy – a randomized controlled study

Abstract: This article describes the results of an eight-month follow-up investigation from a randomized controlled trial of day hospital psychotherapy (DHP) compared with outpatient individual psychotherapy (OIP) for patients with personality disorders (N=114). The patients were randomly assigned to either 18 weeks of day hospital treatment followed by long-term conjoint group and individual therapy (DHP), or outpatient individual psychotherapy (OIP). The main outcome measures were attrition rate, suicide attempts, sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 35 publications
1
45
0
2
Order By: Relevance
“…So until now, hardly any study has addressed possible differences in treatment effectiveness between different settings and across theoretical schools. Exceptions are the studies by Chiesa et al [36,37,38] comparing inpatient treatment and step-down/outpatient treatment and the study by Arnevik et al [39] comparing day hospital treatment and outpatient treatment. …”
Section: Introductionmentioning
confidence: 97%
“…So until now, hardly any study has addressed possible differences in treatment effectiveness between different settings and across theoretical schools. Exceptions are the studies by Chiesa et al [36,37,38] comparing inpatient treatment and step-down/outpatient treatment and the study by Arnevik et al [39] comparing day hospital treatment and outpatient treatment. …”
Section: Introductionmentioning
confidence: 97%
“…Investigators have compared different outpatient treatments [8,9,10,11,12,13], different day hospital treatments [14,15], and different inpatient treatments [16,17]. One recent study in Norway [18] compared outpatient and day hospital treatment for patients with all forms of PD, and found no significant superiority of one treatment over another at 8 months after the start of treatment. However, so far, no study has compared the effectiveness of treatments across widely differing settings and durations.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, UPP was a study including a mixed PD sample, and we have previously reported results for the total sample from the follow-up investigations at 8 months, 18 months, 3 years, and 6 years after the initial random assignment (Antonsen et al, 2014;Arnevik et al, 2009Arnevik et al, , 2010Gullestad et al, 2012). At six-year follow-up, differences between the two treatment conditions were below levels of significance, although different trends were observable (Antonsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Written informed consent was obtained from all included patients, and the project was approved by the Regional Ethics Committee in Norway. The subjects' characteristics, the original trial methodology, and the treatment details have previously been described in greater detail (Arnevik et al, 2009;Gullestad et al, 2012).…”
Section: Setting and Designmentioning
confidence: 99%
See 1 more Smart Citation